2021
DOI: 10.1038/s41598-021-87462-x
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal versus intratracheal exposure to lipopolysaccharides in a murine model of acute respiratory distress syndrome

Abstract: Due to frequent and often severe lung affections caused by COVID-19, murine models of acute respiratory distress syndrome (ARDS) are increasingly used in experimental lung research. The one induced by a single lipopolysaccharide (LPS) exposure is practical. However, whether it is preferable to administer LPS intranasally or intratracheally remains an open question. Herein, female C57Bl/6 J mice were exposed intranasally or intratracheally to one dose of either saline or 3 mg/kg of LPS. They were studied 24 h l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Following whole body plethysmography, respiratory mechanics was assessed using the flexiVent system (SCIREQ) as previously described (Boucher et al., 2021; Khadangi et al., 2021; Mailhot‐Larouche et al ., 2018). The mice were anaesthetized with ketamine and xylazine (100 and 10 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…Following whole body plethysmography, respiratory mechanics was assessed using the flexiVent system (SCIREQ) as previously described (Boucher et al., 2021; Khadangi et al., 2021; Mailhot‐Larouche et al ., 2018). The mice were anaesthetized with ketamine and xylazine (100 and 10 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…LPS is often also used for murine models for acute lung injury also characterized by LPS-induced neutrophilic inflammation (40). However, the concentrations used in these models to induce acute lung injury are ten to fifty times more than used in this model (40)(41)(42) and airway hyperreactivity is often not included in these studies. Interestingly, Khadangi et al showed that no changes in respiratory mechanisms could be observed in their model used for acute lung injury (42).…”
Section: Discussionmentioning
confidence: 99%
“…However, the concentrations used in these models to induce acute lung injury are ten to fifty times more than used in this model (40)(41)(42) and airway hyperreactivity is often not included in these studies. Interestingly, Khadangi et al showed that no changes in respiratory mechanisms could be observed in their model used for acute lung injury (42). By lowering the dose of LPS, we tried to mimic several features of non-allergic asthma with neutrophilic inflammation such as AHR and neutrophilic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“… Direct Lung Damage [ 17 , 22 , 23 ] Route of Application ARDS-Like Affects Antioxidant Approaches Already Used Ref. LPS [ 24 , 25 , 26 ] intranasal/intratracheal instillation lung accumulation of neutrophils, induction of proinflammatory cytokines NAC, SAMC [ 27 , 28 , 29 ] Bacteria [ 30 , 31 , 32 ] intratracheal instillation lung accumulation of neutrophils, induction of proinflammatory cytokines CDC [ 33 ] HCl [ 34 , 35 , 36 ] intratracheal instillation neutrophil infiltration, damage of alveolar/ vascular barrier apocynin, MitoTempo [ 37 , 38 ] Hyperoxia (HALI) [ 39 , 40 , 41 ] intratracheal …”
Section: Methodsmentioning
confidence: 99%